2007
DOI: 10.1182/blood-2006-07-033209
|View full text |Cite
|
Sign up to set email alerts
|

Ubp43 regulates BCR-ABL leukemogenesis via the type 1 interferon receptor signaling

Abstract: Interferon (IFN) signaling induces the expression of interferon-responsive genes and leads to the activation of pathways that are involved in the innate immune response. Ubp43 is an ISG15-specific isopeptidase, the expression of which is activated by IFN. Ubp43 knock-out mice are hypersensitive to IFN-␣/␤ and have enhanced resistance to lethal viral and bacterial infections. Here we show that in addition to protection against foreign pathogens, Ubp43 deficiency increases the resistance to oncogenic transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
1
36
2
Order By: Relevance
“…This was shown by studies demonstrating that, in contrast to wild-type BCR-ABL, a kinasedefective mutant did not suppress formation of Stat complexes and IFN-dependent gene transcription. An interesting possibility is that suppression of Isg15 expression by BCR-ABL may lead to a positive feedback loop leading to suppression of Stat phosphorylation, since ISGylation has been previously linked to the regulation of Stat1 phosphorylation (73), whereas cells lack- ing the ISG15-specific isopeptidase, Ubp43, are more resistant to oncogenic transformation by BCR-ABL (74). However, the validity of such a hypothesis remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 87%
“…This was shown by studies demonstrating that, in contrast to wild-type BCR-ABL, a kinasedefective mutant did not suppress formation of Stat complexes and IFN-dependent gene transcription. An interesting possibility is that suppression of Isg15 expression by BCR-ABL may lead to a positive feedback loop leading to suppression of Stat phosphorylation, since ISGylation has been previously linked to the regulation of Stat1 phosphorylation (73), whereas cells lack- ing the ISG15-specific isopeptidase, Ubp43, are more resistant to oncogenic transformation by BCR-ABL (74). However, the validity of such a hypothesis remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 87%
“…USP18, which negatively regulates the innate immune response against viral infections, was shown to be involved in such host genes (27). Studies on USP18-deficient mice showed that increasing the immunoactivity of ISG15 made the mice resistant against viral and bacterial infections (28,41,51), yet the mechanism of USP18 induction in infected hosts is controversial. One possible mechanism is a negative-feedback reaction against overexpression of the ISG15 gene, accompanied by a protective response after viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Within this respect, it has been recently shown that, in a mouse model, USP18/Ubp43 absence improves the resistance to oncogenic transformation by BCR-ABL. This resistance to leukemic development is dependent on type I IFN signaling (36).…”
Section: Discussionmentioning
confidence: 99%